Impact of ayurvedic panchakarma along with lifestyle modification in restoring glucose tolerance in type 2 diabetics - Kshirsagar, Jyoti; Lakariya, Asha; Khan, Sadik (International Journal of Basic & Clinical Pharmacology, 2024)
Background: Diabetes mellitus is an increasing global concern. There is limited published literature documenting the effectiveness of Ayurveda interventions for this condition. Aim of the study was to evaluate the effect of the comprehensive diabetes care (CDC) program on glycosylated hemoglobin (HbA1c), body mass index (BMI), body weight, abdominal girth, and dependency om conventional medication in patients with diabetes mellitus. Methods: A retrospective, observational, single centre study was conducted at Madhavbaug clinic, India from August 2021 to March 2023. Patients aged 18 years and above with a diagnosis of diabetes mellitus were included in this study. Follow-up was conducted at day 1, 30, 60, and 90. Results: A total of 39 patients were assessed, of which 18 (46.2%) patients were male. The mean HbA1c levels at day 1, 30, 60, and 90 for the 12 patients with HbA1c<6.5 was 6.23±0.24%, 5.75±0.41%, 5.60±0.33%, and 5.65±0.30%, respectively. The mean HbA1c levels at day 1, 30, 60, and 90 for the 22 patients with HbA1c 6.6-9.0 was 7.14±0.48%, 6.46±0.62%, 6.22±0.59%, and 6.12±0.42%, respectively. The mean HbA1c levels at day 1, 30, 60, and 90 for the 3 patients with HbA1c >9.0 was 10.30±0.45%, 9.10±1.20%, 7.30±1.50%, and 7.15±0.65%, respectively. Conclusions: Ayurvedic panchakarma along with lifestyle modification is successful in restoring the glucose tolerance in type 2 diabetic patients.